Impact of obesity, fasting plasma glucose level, blood pressure, and renal function on the severity of COVID-19: A matter of sexual dimorphism?. (December 2020) - Huh, Kyungmin; Lee, Rugyeom; Ji, Wonjun; Kang, Minsun; Hwang, In Cheol; Lee, Dae Ho; Jung, Jaehun
Abstract: Aims: This study aimed to assess whether body mass index (BMI), fasting plasma glucose (FPG) levels, blood pressure (BP), and kidney function were associated with the risk of severe disease or death in patients with COVID-19. Methods: Data on candidate risk factors were extracted from patients' last checkup records. Propensity score-matched cohorts were constructed, and logistic regression models were used to adjust for age, sex, and comorbidities. The primary outcome was death or severe COVID-19, defined as requiring supplementary oxygen or higher ventilatory support. Results: Among 7, 649 patients with confirmed COVID-19, 2, 231 (29.2%) received checkups and severe COVID-19 occurred in 307 patients (13.8%). A BMI of 25.0–29.9 was associated with the outcome among women (aOR, 2.29; 95% CI, 1.41–3.73) and patients aged 50–69 years (aOR, 1.64; 95% CI, 1.06–2.54). An FPG ≥ 126 mg/dL was associated with poor outcomes in women (aOR, 2.06; 95% CI, 1.13–3.77) but not in men. Similarly, estimated glomerular filtration rate (eGFR) < 60 ml/min/1.73 m 2 was a risk factor in women (aOR, 3.46; 95% CI, 1.71–7.01) and patients aged < 70 years. Conclusions: The effects of BMI, FPG, and eGFR on outcomes associated with COVID-19 were prominent in women but not in men.